Evaluasi Kebutuhan Ruang Parkir Pada Rumah Sakit Kelas C Di Kota Palangka Raya - Ari Widya Permana; Noviyanthy Handayani; Norseta Ajie Saputra (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Yasmin Mother and Child Hospital in Palangkaraya City is one of the Class C Hospitals in Central Kalimantan. Yasmin Hospital has become one of the most visited hospitals every day. During visiting hours there was an increase in the need for parking spaces at Yasmin RSIA, so that vehicles that would not use the parking area were not accommodated. This study aims to evaluate the capacity of the parking lot at the RSIA Yasmin Palangka Raya City and provide suggestions for improvement to the Yasmin RSIA. Primary data were obtained from direct observations which included measurements of the number of parking lots, parking area, time count and circulation of the number of vehicles. Furthermore, the data were analyzed to obtain parking characteristics which include parking volume, parking accumulation, parking duration, parking change, parking capacity, and parking index. Based on the results of the analysis, the maximum accumulated vehicle parking occurs on Monday, the motorcycle parking index exceeds 100%, meaning that parking needs exceed normal parking capacity. The proposed improvement is to use the basement as a parking lot to increase the capacity of parking spaces and to arrange parking patterns and parking circulation